A novel peroxidase from white-rot Agaricomycetes fungus Phlebia radiata strain KB-DZ15: Its purification, characterisation, and potential application for dye-decolorisation and lignin-biodegradation. Issue 5 (3rd September 2022) - Bouacem, Khelifa; Allala, Fawzi; Zaraî Jaouadi, Nadia; Hamdi, Sondes; Mechri, Sondes; Ighilahriz, Kahina; Rekik, Hatem; Hacene, Hocine; Bouanane-Darenfed, Amel; Jaouadi, Bassem
Abstract: A novel extracellular lignin peroxidase (LiP) has been produced (65 U/mL) in potato dextrose broth (PDB)-optimized media by a white-rot Agaricomycetes fungus strain KB-DZ15 newly isolated from dead deciduous trees at Zimoula Forest (Tizi-Ouzou, Algeria). This strain was identified as Phlebia radiata based on internal transcribed spacer (ITS) rDNA gene sequencing. The peroxidase enzyme (called LiP PR40) was purified and characterised. The matrix-assisted laser desorption-ionization – time of flight mass spectrometry (MALDI-TOF/MS) analysis revealed that LiP PR40 enzyme was a monomer with a molecular mass of 40, 125.31 Da. The 25 N-terminal residue sequence of LiP PR40 showed high similarity with those of fungi LiPs. Interestingly, LiP PR40 presents premium activity at pH 3 and 80 °C with specific activity and Reinheitzahl (RZ) level of 510 U/mg and 2.81, respectively. Furthermore, it was completely inhibited by sodium azide (NaN3 ) and potassium cyanide (KCN), suggesting the presence of haem components in its tertiary structure. More interestingly, LiP PR40 illustrated more upper catalytic efficiency and dye-decolorisation aptitude than that of commercial well-known horseradish peroxidase (HRP) from roots of Armoracia rustanica and the purified reported LiP BA45 from Bjerkandera adusta strain CX-9. Consequently, these properties make LiP PR40 a potential candidate for destaining synthetic-dyes and lignin-biodegradation. Graphical Abstract: UF0001